Combined use of vancomycin-modified Ag-coated magnetic nanoparticles and secondary enhanced nanoparticles for rapid surface-enhanced Raman scattering detection of bacteria - Wang CW (Dove Medical Press, 2018)
Chongwen Wang,1,2,* Bing Gu,3,4,* Qiqi Liu,1,* Yuanfeng Pang,2,5 Rui Xiao,1 Shengqi Wang1–3 1Beijing Key Laboratory of New Molecular Diagnosis Technologies for Infectious Diseases, Beijing Institute of Radiation Medicine, Beijing, People’s Republic of China; 2College of Life Sciences and Bio-Engineering, Beijing University of Technology, Beijing, People’s Republic of China; 3Medical Technology School, Xuzhou Medical University, Xuzhou, People’s Republic of China; 4Department of Laboratory Medicine, Affiliated Hospital of Xuzhou Medical University, Xuzhou, People’s Republic of China; 5Department of Toxicology, Capital Medical University, Beijing, People’s Republic of China *These authors contributed equally to this work Background: Pathogenic bacteria have always been a significant threat to human health. The detection of pathogens needs to be rapid, accurate, and convenient. Methods: We present a sensitive surface-enhanced Raman scattering (SERS) biosensor based on the combination of vancomycin-modified Ag-coated magnetic nanoparticles (Fe3O4@Ag-Van MNPs) and Au@Ag nanoparticles (NPs) that can effectively capture and discriminate bacterial pathogens from solution. The high-performance Fe3O4@Ag MNPs were modified with vancomycin and used as bacteria capturer for magnetic separation and enrichment. The modified MNPS were found to exhibit strong affinity with a broad range of Gram-positive and Gram-negative bacteria. After separating and rinsing bacteria, Fe3O4@Ag-Van MNPs and Au@Ag NPs were synergistically used to construct a very large number of hot spots on bacteria cells, leading to ultrasensitive SERS detection. Results: The dominant merits of our dual enhanced strategy included high bacterial-capture efficiency (>65%) within a wide pH range (pH 3.0–11.0), a short assay time (<30 min), and a low detection limit (5×102 cells/mL). Moreover, the spiked tests show that this method is still valid in milk and blood samples. Owing to these capabilities, the combined system enabled the sensitive and specific discrimination of different pathogens in complex solution, as verified by its detection of Gram-positive bacterium Escherichia coli, Gram-positive bacterium Staphylococcus aureus, and methicillin-resistant S. aureus. Conclusion: This method has great potential for field applications in food safety, environmental monitoring, and infectious disease diagnosis. Keywords: surface-enhanced Raman scattering, Fe3O4@Ag magnetic nanoparticle, Au@Ag nanoparticles, vancomycin-modified, rapid bacteria detection